Qatargate and lobbying crisis in the European Union. Media analysis and regulatory challenges for institutional transparency - Fernández-Torres, María Jesús; Chamizo-Sánchez, Rocío (Frontiers in Political Science, 2025)
The lobby seeks to influence public policy decisions, requiring this influence to remain free of irregular practices to be legitimate. This research is contextualized in one of the most important sporting events of 2022, the Qatar Soccer World Cup, organized by FIFA and taking place from 20 November to 18 December 2022. The case study focuses on the Qatargate scandal, a plot investigated by the Belgian police for alleged bribes from Qatar and other countries to MEPs and senior civil servants to influence political decisions and to downplay human rights abuses in the World Cup host country. Qatargate was the tip of the iceberg for many of those who study decision-making in Europe, causing an unprecedented commotion within the European Union and exposing the vulnerabilities of the lobbying sector and the need for a solvent regulatory framework that would guarantee transparency and the legitimacy of lobbying as a necessary part of democratic processes, avoiding and punishing all corrupt practices. The objective of this research focuses on analyzing the informative treatment of the Qatargate case in the Spanish press, identifying the media framing given to this corruption case and how the selected media report on said scandal. At the same time, it is also intended to know if these frameworks address the role that certain institutions have in promoting transparency in the European Union and if sufficient regulatory measures are required to provide standardized systems that allow the promotion of transparency and good practice in the lobbying sector.